2008
DOI: 10.1302/0301-620x.90b11.20695
|View full text |Cite
|
Sign up to set email alerts
|

Primary open reduction and fixation compared with delayed corrective arthrodesis in the treatment of tarsometatarsal (Lisfranc) fracture dislocation

Abstract: Fracture-dislocations of the tarsometatarsal (Lisfranc) joints are frequently overlooked or misdiagnosed at initial presentation. This is a comparative cohort study over a period of five years comparing primary open reduction and internal fixation in 22 patients (23 feet) with secondary corrective arthrodesis in 22 patients (22 feet) who presented with painful malunion at a mean of 22 months (1.5 to 45) after injury. In the first group primary treatment by open reduction and internal fixation for eight weeks w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
128
1
15

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(147 citation statements)
references
References 38 publications
0
128
1
15
Order By: Relevance
“…They pooled the results of all reported AOFAS scores within the literature and found the mean score to be 78.1. Since 2010, several case series have been published with mean scores similar or higher than that reported by Stavlas et al One other comparative trial was found comparing primary ORIF with delayed fusion [22]. This well-designed study compared the results of 22 primary fixations with 22 delayed fusions at a mean of 22 months postinjury.…”
Section: Discussionmentioning
confidence: 89%
“…They pooled the results of all reported AOFAS scores within the literature and found the mean score to be 78.1. Since 2010, several case series have been published with mean scores similar or higher than that reported by Stavlas et al One other comparative trial was found comparing primary ORIF with delayed fusion [22]. This well-designed study compared the results of 22 primary fixations with 22 delayed fusions at a mean of 22 months postinjury.…”
Section: Discussionmentioning
confidence: 89%
“…A total of 11 papers satisfied the inclusion criteria and received critical analysis [2,11,17,21,23,30,31,33,34,38,39]. There were seven case series retrospective studies [2,17,30,31,33,38,39], two comparative cohort studies [23,34], and two prospective randomised control trials-comparative studies [11,21].…”
Section: Resultsmentioning
confidence: 99%
“…From the latter four studies only the data from the groups of patients who were treated by internal fixation were included in the review. In nine articles [2,11,17,21,23,30,33,34,39] there was no difference in the evaluation process, and in the remaining two papers [31,38] there was one point of difference in the quality scoring process, which was not significant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations